Thermos-responsive hydrogel system encapsulated engineered exosomes attenuate inflammation and oxidative damage in acute spinal cord injury - Xiao, Yu; Hu, Xinmei; Jiang, Peng; Qi, Zhongquan (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Spinal cord injury (SCI) is a serious and disabling condition, and the effectiveness of conventional treatment is limited, such as supportive treatment and emergency surgery. Exosomes derived from umbilical cord mesenchymal stem cells (UCMSC-Exos) have potential therapeutic effects on SCI but are limited by delivery efficiency. Our study aimed to further investigate the therapeutic effects of miR-138-modified UCMSC-exosomes (Exos-138) following SCI. Methods: We developed an injectable triblock polymer of polyglycolic acid copolymer and polyethylene glycol (PLGA-PEG-PLGA)-loaded temperature-sensitive hydrogel of miR-138-modified stem cell exosomes and characterised its biocompatibility in vitro. In Sprague-Dawley rats with SCI, the hydrogel was injected into the injury site, behavioural scores were measured, and pathological analysis was conducted postoperatively to assess neurological recovery. Results:In vitro, our data demonstrated that miR-138-5p-modified UCMSC-Exos can reduce inflammation levels in BV-2 cells through the NLRP3-caspase1 signalling pathway and reduce neuronal apoptosis by downregulating intracellular reactive oxygen species levels through the Nrf2-keap1 signalling cascade. The results of in vivo experiments showed that the P-Exos-138 hydrogel promoted neurological recovery in rats with SCI. Discussion: Our study explored a novel exosome delivery system that can be a potential therapeutic strategy for SCI. Our study, currently, has theoretical value; however, it can serve as a basis for further investigations on the treatment approaches at various stages of SCI development in inflammation-dependent injury of the central nervous system.